Drugs as important factors causing allergies - Żukiewicz-Sobczak, Wioletta A.; Wróblewska, Paula; Adamczuk, Piotr; Zwoliński, Jacek; Oniszczuk, Anna; Wojtyła-Buciora, Paulina; Silny, Wojciech (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2015)
Medications can cause many adverse reactions, both non-immunologic and immunologic ones. Allergies can take many forms, allergic reactions include all types of reactions according to Gell and Coombs. Typically, allergic reactions to drugs are manifested by skin lesions such as maculopapular rash or urticaria and life-threatening systemic reactions such as anaphylaxis. Allergy to drugs is diagnosed based on medical history and a number of specific tests: skin tests, blood tests. In diagnosing the causes of anaphylaxis, the basophil activation test is used to exclude false negative and false positive results of skin tests and specific IgE levels. Allergic reactions to medications usually resolve themselves after discontinuation of the drug. Sometimes in the treatment anti-allergic drugs are used to inhibit the development of skin lesions. After observing any signs of drug allergy it is important to accurately diagnose the cause, since the subsequent exposure to the drug may lead to a strong anaphylactic reaction and consequently death.